Does fish price depend solely on weight? A market survey analysis from four districts of West Bengal, India - Debjit Das; Soumalya Mukhopadhyay; Adity Sarbajna; Suman Bhusan Chakraborty (Journal of Fisheries, 2020)
Fish is an important food item that contains perfect combination of essential nutrients. The main consumable fishes in West Bengal, India are various carps and other small indigenous fishes. The objective of the study was to find out whether fish weight was a crucial factor to decide pricing and what kind of fish was beneficial for consumer from economic perspective. Thirteen markets in four districts (Kolkata, North and South 24 Parganas, Howrah) of West Bengal were surveyed to collect information about price, weight and number of vendors selling a particular fish considering 22 fish species. Subsequent statistical analyses were performed to conclude about the relationship between fish weight and price. The study indicates that pricing of every fish species does not depend solely on their weight. Weight plays important role to determine the price of few fish species such as Liza persia, Lates calcarifer, Wallago attu, Ompok pabo and Mystus tengara. But, the price of small indigenous fishes like Chanda nama, Colisa fasciata, Harpadon nehereus, Monopterus cuchia, Rhingomugil corsula, Sperata aor and Puntius puntio does not depend on the weight of individual fish. Seasonal availability, taste, consumer’s personal preference have important role to determine fish price.